Pharmacokinetics of anidulafungin in two critically ill patients with septic shock undergoing CVVH. (December 2013) - De Rosa, Francesco G.; Corcione, Silvia; Baietto, Lorena; Pasero, Daniela; Perri, Giovanni Di; Marco Ranieri, V.; D'Avolio, Antonio
<x content-type="archive" xml:space="preserve">Abstract</x> Candidemia is associated with high mortality rate especially in critically ill (ICU) patients with septic shock and echinocandins such as anidulafungin are recommended as first-line treatment. Available pharmacokinetic studies of anidulafungin in healthy volunteers and in patients with renal or hepatic impairment showed that no dose adjustment is needed even in patients receiving standard intermittent haemodialysis. However, few data are available with continuous veno-venous haemofiltration (CVVH). In this study, the pharmacokinetic of anidulafungin was studied in two ICU patients with candidemia and septic shock undergoing CVVH. Both patients had satisfactory parameters of Cmax (9·04 and 5·68 mg/l, respectively), area under the curve (AUC) (95·18 and 67·48 mg/l h) and Cmin (2·61 and 1·43 mg/l). AUC/MIC ratio and Cmax/MIC values were: 11887 and 8435; 1130·25 and 710, for patients 1 and 2, respectively. Our data confirm that in patients with septic shock anidulafungin presents only mild pharmacokinetic changes compared to data reported during CVVH alone.